2013
DOI: 10.12816/0003203
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Pass-Fail Outcomes with Psychological Health of First-Year Medical Students in a Malaysian Medical School

Abstract: Objectives:The demanding and intense environment of medical training can create excessive pressures on medical students that eventually lead to unfavorable consequences, either at a personal or professional level. These consequences can include poor academic performance and impaired cognitive ability. This study was designed to explore associations between pass-fail outcome and psychological health parameters (i.e. stress, anxiety, and depression symptoms). Methods: A cross-sectional study was conducted on a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 41 publications
0
43
1
1
Order By: Relevance
“…In bivariate analysis, the use of skin lightening products and poor academic performance were found to be associated with depression. Previous studies found that depression deteriorates cognitive functioning (Yusoff, 2013). The use of skin lightening products and its relation to depression would need further investigation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In bivariate analysis, the use of skin lightening products and poor academic performance were found to be associated with depression. Previous studies found that depression deteriorates cognitive functioning (Yusoff, 2013). The use of skin lightening products and its relation to depression would need further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Factors increasing the risk of depression in university students have been identified as follows: 1) sociodemographic factors such as older age or higher study year (Chen et al, 2013;, female gender , lower socioeconomic status (Chen et al, 2013;Ibrahim et al, 2012;Steptoe, Tsuda, Tanaka, & Wardle, 2007); 2) stressful and traumatic life events including life stressors (Afewuya et al, 2006; Reyes-Rodríguez, Rivera-Medina, Cámara-Fuentes, Suárez-Torres, & Bernal, 2013), gender-based violence (Gelaye, Arnold, Williams, Goshu, & Berhane, 2009), witnessing parental violence (Nicodimos, Gelaye, Williams, & Berhane, 2009), and posttraumatic stress disorder (Peltzer, 1998); 3) addictive behaviour including high level of alcohol consumption Peltzer, 2003), smoking (Adewuya, 2006;Adewuya et al, 2006), and gambling (Moode, & Finnigan, 2006); 4) other health risk behaviour such as physical inactivity (Taliaferro, Rienzo, Pigg, Miller, & Dodd, 2009), overweight or obesity (Wilson, Gallivan, Kratzke, & Amatya, 2012;Zhao et al, 2009), HIV risk behaviour (Agardh, Canto-Graae, Ostergren, 2012;Lundberg et al, 2011), sleeping problems (Angelone, Mattei, Sbarbati, & Di Orio, 2011), nonfatal unintentional injury (Chen, Deng, Chn, Kelleher, & Xiang, 2005), and use of skin lightening products (Ladizinski, Mistry, & Kundu, 2011); 5) social variables including social support (Kim, 2001), religiosity and/or spirituality (Berry & York, 2011), low sense of control (Steptoe et al, 2007); and 6) poor academic performance (Yusoff, 2013). among undergraduate students of Obafemi Awolowo University in Nigeria.…”
mentioning
confidence: 99%
“…Among Malaysian students, the prevalence of moderate depression found 27.5% and 9.7% found as severe or extremely severe depression [8]. Various risk factors for depression among university students have been identified such as higher study year [18,19], lower socioeconomic status [17,19], poor academic performance and life satisfaction [20], high level of alcohol consumption, smoking [21,22], gambling [23], social support [24], life stressors [25], post-traumatic stress disorder [26], physical inactivity [27], overweight or obesity [28] and sleeping problems [29]. University students are a special group of people in critical transition from adolescence to adulthood and one of the most stressful moments in a person's life.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high prevalence of depression and anxiety symptoms among medical students, medical education is recognized as a stressful environment, and the consequences have been extensively investigated (3,(6)(7)(8). First, mental health problems during medical education could exert a negative effect on the academic performance, physical health and psychosocial well-being of students.…”
Section: Introductionmentioning
confidence: 99%